Penggunaan Media Pembelajaran Spinning Wheel Pada Mata Pelajaran Bahasa Inggris Di SD Negeri Cibogo - Prasetyo, Teguh; Brawijaya , Andri; Fitriliani, Aulya; Kurniawati, Siti (INCOME: Indonesian Journal of Community Service and Engagement, 2022)
This English lesson is taught because it is considered that early childhood is easy to catch new things. The digital age demands, all in English, also encourage children to learn foreign languages and supplement local content at the elementary school level. However, at Elementary School Cibogo, Tugu Jaya Village, Cigombong District, English lessons are still not going well due to the lack of educators (teachers) who master English, so students are still very unfamiliar with English. English tutoring and making Spinning Wheel learning media for English subjects are one of the efforts to assist teachers in conveying English material efficiently to students and introducing English to students. The method of implementing the service consists of the stages of preparation, implementation, and evaluation/reflection of activities. Supporting techniques for the preparation of community service reports are written using techniques, namely observation, and interviews. After the application of the Spinning Wheel media in grade 4 resulted in students becoming enthusiastic when the English learning process took place, it was seen that the students often asked questions about various vocabularies that they did not know. In conclusion, students will be enthusiastic if there is a learning media because it will attract their attention, and this Spinning Wheel is also enough to help teachers. However, teachers also need to deepen the English material).